Testing the contribution, accuracy and performance of MGEX (GNSS (GPS+GLONASS+GALILEO+BEIDOU+QZSS)) positioning in the study region - Pırtı, Atınç (Geodesy and Cartography, 2023)
The European Commission (EC) originally proposed ideas for a European Galileo satellite navigation system in 1999. A four-phase development is planned, involving investment from both the public and commercial sectors. Galileo is intended for both public and government use; the system is administered and operated by civil administration. Galileo will consist of a constellation of 30 satellites, a number of globally situated ground stations, and a ground control and monitoring system – all of which are quite similar to the structure, format, and layout of GPS. This document discusses an experiment at the project site that used the static approach to integrate GPS, GLONASS, GALILEO, Beidou, and QZSS signals. This research analyses the possible precision of GPS-only and GPS/GLONASS/GALILEO/Beidou/QZSS. These results suggest that combining a GPS system with GALILEO, GLONASS Beidou, and QZSS is preferable for surveying purposes. Integrating GPS/GLONASS/GALILEO/Beidou/QZSS static measurements in the study region with 0–120 millimetre accuracy looks to be possible in three days.